Health beliefs and attitudes toward Influenza and COVID-19 vaccination in Portugal: a study using a mixed-method approach - Santos, Ana João; Kislaya, Irina; Matias-Dias, Carlos; Machado, Ausenda (Frontiers in Public Health, 2024)
Introduction Vaccination is one of the most effective population strategies to prevent infectious diseases and mitigate pandemics, and it is important to understand vaccine uptake determinants since vaccine hesitancy has been increasing for the past few decades. The Health Belief Model (HBM) has been widely used for understanding vaccination behavior. The current study aimed to assess influenza vaccine (IV) non-uptake and attitudes toward COVID-19 vaccination, two important respiratory diseases with similar symptoms, and routes of transmission in the Portuguese population. Methods We conducted a cross-sectional study using a panel sample of randomly chosen Portuguese households. A total of 1,050 individuals aged 18 years and over responded to a telephone or online questionnaire. Through a mixed-method approach, we employed thematic content analysis to describe reasons for not taking the IV, considering the HBM dimensions, and quantitative statistical analysis to estimate IV and COVID-19 vaccine coverage. Results The IV uptake for the overall population was 30.7% (CI 95%: 26.5, 35.2). Susceptibility was found to be a main factor for IV non-uptake, followed by barriers, such as stock availability and fear of adverse effects. The uptake of the COVID-19 vaccine was very high in the study population (83.1%, CI 95%: 13.6%−20.9%). There was a high perception of COVID-19-associated severity and fear of the consequences. Individuals who reported IV uptake seemed to perceive a higher severity of COVID-19 and a higher benefit of taking the COVID-19 vaccine for severe complications. Discussion Thus, the population does not seem to consider influenza to be a health risk, as opposed to COVID-19, which is considered to be a possibly severe disease. The association between IV uptake and COVID-19 perceptions highlights that an overall attitude toward vaccination in general may be an important individual determinant.